Capital Structure Dynamics Of Select Oil And Gas Firms Listed In NSE Sectoral Indices (International Journal of Environmental Sciences, 2025)
This study examines the capital structure dynamics of selected oil and gas firms listed on the National Stock Exchange (NSE) sectoral indices in India. Given the capital-intensive nature and strategic importance of the oil and gas sector, understanding financing patterns is critical for financial stability and policy formulation. This study examines the longitudinal data of 2016 to 2023 in the parameter of levels of debt-to-equity ratio, level of asset tangibility, ownership structure and exposure to macroeconomic volatility of the public and the private sector firms. Using statistical variables such as regression analysis and correlation matrices, the research finds that the capital strategies of the public sector undertakings are more conservative and policy based whereas the objective of the privately owned firms is aggressive and market based. Important results show that profitability, firm size and oil price volatility influence the leverage decisions to a great extent. The findings are also indicative of an increasingly engaged growth towards the hybridization of financial instruments and ESG-linked financing due to the changing energy and sustainability objectives. The implications of these insights to investment and corporate managers seeking to exercise best capital decision making in the highly regulated and fluctuating environment are essential to the investors and policymakers.